Conversational narrative : storytelling in everyday talk - Norrick, Neal R. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2000)
This book investigates the forms and functions of storytelling in everyday conversation. It develops a rhetoric of everyday storytelling through an integrated approach to both the internal structure and the contextual integration of narrative passages. It aims at a more complete picture of oral narrative through analysis of a wider range of natural data, including personal anecdotes told for humor, put-down stories told for self-aggrandizement, family stories retold to ratify membership and so on, as well as marginal stories and narrative-like passages to delineate the boundaries of conversati.